A Companion to Dwight D. Eisenhower - 4 0 16; Pach, Chester J.; 5 (Malden, MA : Wiley-Blackwell, 2017)
The essays in this volume analyze the rich historiography of the Eisenhower years, provide thoughtful and sometimes provocative assessments, and encourage readers to think about the connections between past and present--
INTRODUCTION / Chester J Pach -- GENERAL OF THE ARMY. YEARS OF PREPARATION, 1890-1941 / Jonathan Reed Winkler -- EISENHOWER IN WORLD WAR II / Nicholas Evan Sarantakes -- EISENHOWER AND THE ONSET OF THE COLD WAR, 1945-1949 / Thomas Bruscino -- EISENHOWER AS NATO COMMANDER / Andrew M Johnston -- PRESIDENT. THE BABY BOOM, YOUTH CULTURE, AND FAMILY LIFE / Carolyn Herbst Lewis -- CITIES AND SUBURBS IN THE EISENHOWER ERA / Amy L Scott -- AMERICAN POLITICS AT MID-CENTURY / Gary W Reichard -- EISENHOWER REPUBLICANISM / Steven Wagner -- LEADERSHIP AND DECISION-MAKING / Richard V Damms -- EISENHOWER, THE RED SCARE, AND DOMESTIC ANTICOMMUNISM / Andrew J Falk -- EISENHOWER AND AFRICAN AMERICAN CIVIL RIGHTS / David A Nichols -- MANAGING THE ECONOMY / Iwan Morgan -- EISENHOWER AND SOCIAL WELFARE / Andrew Morris -- NATURAL RESOURCES, CONSERVATION, AND THE ENVIRONMENT / J Brooks Flippen -- EISENHOWER AND THE KOREAN WAR / James I Matray -- EISENHOWER'S NATIONAL SECURITY POLICIES / David L Snead -- EISENHOWER, NUCLEAR WEAPONS, AND ARMS CONTROL / Philip Nash -- EISENHOWER, THE CIA, AND COVERT ACTION / James Callanan -- PROPAGANDA AND PUBLIC DIPLOMACY / Kenneth Osgood -- NATO, WESTERN EUROPE, AND THE EISENHOWER ADMINISTRATION / Robert T Davis -- SPECIAL OR NOT SO SPECIAL? ANGLO-AMERICAN RELATIONS / Michael F Hopkins -- EISENHOWER AND LATIN AMERICA / Stephen G Rabe -- EISENHOWER, CHINA, AND TAIWAN / Scott Kaufman -- EISENHOWER AND THE THIRD WORLD / Kevin E Grimm -- EISENHOWER, INDOCHINA, AND VIETNAM / Kathryn C Statler -- THE ARAB-ISRAELI DISPUTE AND THE MIDDLE EAST / Peter L Hahn -- CITIZEN. AFTER THE PRESIDENCY / Stephen T Pfeffer.
Includes bibliographical references and index.
Print version record.
Keywords: 2 -- Eisenhower, Dwight D. -- 0 -- 1890-1969.; 6; 1953-1961; Presidents -- United States -- 20 -- Biography; Politics and government -- United States -- 1953-1961.20; Biography.;Electronic books